1992
DOI: 10.1007/bf00175469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of neuropeptide K and neuropeptide γ with neurokinin A at NK2 receptors in the hamster urinary bladder

Abstract: Neuropeptide K (NPK) and neuropeptide gamma (NP gamma) are two endogenous N-terminally extended forms of neurokinin A (NKA). Here, we compared their effects with those of NKA on 125I-NKA binding, phosphatidylinositol (PI) turnover and smooth muscle contraction in the hamster urinary bladder. NPK, NP gamma and NKA were equipotent in competing 125I-NKA from NK2 receptors in crude hamster bladder membranes. All three peptides stimulated PI turnover by approximately 750% with similar potency. In a third series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In the hamster urinary bladder, the pharmacological profile of NPy was similar to that of NKA and NPK on NK2 receptor binding stimulation of phosphatidylinositol hydrolysis and smooth muscle contraction (van Giersbergen et al, 1992). Moreover, NPy was one of the most potent tachykinins to contract the human isolated bronchus (Burcher et al, 1991) and to increase guinea-pig total lung resistance (Yuan et al, 1994).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the hamster urinary bladder, the pharmacological profile of NPy was similar to that of NKA and NPK on NK2 receptor binding stimulation of phosphatidylinositol hydrolysis and smooth muscle contraction (van Giersbergen et al, 1992). Moreover, NPy was one of the most potent tachykinins to contract the human isolated bronchus (Burcher et al, 1991) and to increase guinea-pig total lung resistance (Yuan et al, 1994).…”
Section: Introductionmentioning
confidence: 84%
“…Surprisingly, the order of potency for these natural tachykinins on the cardiovascular system after central administration is NPK > NPy > SP > NKA > NKB (Couture et al, 1995). Therefore, the most potent tachykinins are the N-extended forms of NKA which have been considered as NK2 agonists in several biological and binding assays (Beaujouan et al, 1988;Takeda & Krause, 1989;Dam et al, 1990c;Van Giersbergen et al, 1992). We may relate this finding to the greater metabolic stability of NPK and NPy due to their longer N-terminal amino acid sequence (Takeda & Krause, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, NK2 receptor mRNA has been reported to be either undetectable (Tsuchida et al, 1990) or present in a very low amount in the rat spinal cord whereas NKI receptor mRNA was detected by the mRNA blot hybridization technique (Tsuchida et al, 1990). Since its discovery, NPy has been considered to be a selective NK2 agonist in binding assays Badgery-Parker et al, 1993;Zeng et al, 1994) and this peptide has been used in vivo and in vitro to substantiate the presence of NK2 receptors (Kalra et al, 1992;Van Giersbergen et al, 1992;Qian et al, 1994;Zeng et al, 1994). To our knowledge, our study is the first to show that NPy behaves as a potent NKI agonist in functional studies in the CNS.…”
Section: Effects Of Adrenoceptor Inhibitors On the Cardiovascular Resmentioning
confidence: 99%
“…While NPy is active in the low pmol range by the i.c.v. route (Picard & Couture, 1995) (Beaujouan et al, 1988;Van Giersbergen et al, 1992), yet the cardiovascular responses induced by i.t. and i.c.v.…”
Section: Effects Of Adrenoceptor Inhibitors On the Cardiovascular Resmentioning
confidence: 99%
“…In this species, the activation of tachykinin NK 2 receptors causes a contraction of the urinary bladder smooth muscle (Watson et al 1983;Dion et al 1987) which is sustained by stimulation of inositol phospholipid hydrolysis (Bristow et al 1987;Suman-Chauhuan et al 1990). Tachykinin NK 2 receptors in the hamster bladder have also been extensively characterized by radioligand binding (Lee et al 1986;Van Giersbergen et al 1992;Guard et al 1993;Goso et al 1995): at autoradiography, a high density of NK 2 receptors was observed in the smooth muscle layer and, to a minor extent, in the bladder epithelium (Burcher and Buck 1986). Moreover, the NK 2 receptor from the hamster urinary bladder has been cloned and its pharmacological properties analyzed after expression in host cells (Aharony et al 1994).…”
Section: Introductionmentioning
confidence: 99%